2019
DOI: 10.5430/ijh.v5n2p21
|View full text |Cite
|
Sign up to set email alerts
|

Presence and influence of trauma in inpatient psychiatric care

Abstract: Background: Previous research indicates traumatic exposure and posttraumatic stress disorder (PTSD) occur at a higher rate in people with severe mental illness (SMI) than in the general population, and co-occurring PTSD symptoms can worsen outcomes for patients with SMI.Objective: This study assessed the presence and influence of PTSD symptoms in individuals with SMI in an inpatient psychiatric setting, and rates of PTSD diagnoses in this population.Methods: Retrospective analysis of demographic information an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This study altered the lookback time of the PHQ-9 from the standard two weeks to one week to better match inpatient settings' lengths of stay, a reliable and valid alteration per previous analyses. 28 The PHQ-9 is intended for adults, and a modified version (PHQ-A) was used with adolescent patients. 29…”
Section: Methodsmentioning
confidence: 99%
“…This study altered the lookback time of the PHQ-9 from the standard two weeks to one week to better match inpatient settings' lengths of stay, a reliable and valid alteration per previous analyses. 28 The PHQ-9 is intended for adults, and a modified version (PHQ-A) was used with adolescent patients. 29…”
Section: Methodsmentioning
confidence: 99%
“…Within recent research examining the prevalence of PTSD experienced by patients accessing psychiatric inpatients units, it has been found that the majority (65.7%) had high scores on the Abbreviated PTSD Checklist (PCL-C), indicating a high likelihood of PTSD (Nowlin & Brown, 2019). For this reason, it is important that effective trauma interventions, which can be implemented to support those in inpatient mental health settings, are developed.…”
Section: Emdr In Inpatient Mental Health Settingsmentioning
confidence: 99%